Rancang Bangun Aplikasi Penjadwalan Pengajaran Guru Di Smp Islam Al - Istiqomah Menggunakan Algoritma Genetika (Studi Kasus Smp Islam Al-Istiqomah Depok) - Saif Khaidir Ali; Saprudin (CV. Multi Kreasi Media, 2024)
Abstract− The application for scheduling teaching and learning activities using a genetic algorithm was designed and built due to problems that occurred during the process of making schedules at the Al Istiqomah Islamic Middle School, Depok. for approximately three days, apart from that the schedule that has been made is also prone to errors, namely the formation of a clashing condition when a predetermined limit or obstacle is violated. The genetic algorithm applied to the designed and built application is expected to make it easier to overcome these problems by shortening the schedule creation process and minimizing the occurrence of conflicting conditions on the schedule. This application is web-based, using the programming language HTML, PHP and MySQL database. The system development method wartefall). Based on the test results at the same iteration involving different Crossover Probability (????????) and Mutation Probability (????????) values, this application can shorten the manufacturing schedule process and minimize the number of conflicts that occur. The feature for Schedule Swap in the application makes it possible to further minimize conflicting conditions that occur.